Molecular Imaging Reveals a Role for AKT in Resistance to Cisplatin for Ovarian Endometrioid Adenocarcinoma - Wang, Hanxiao (2012)
PURPOSE: Ovarian cancer is the fifth leading cause of cancer deaths among American women. Platinum-based chemotherapy, such as cisplatin, represents the standard of care for ovarian cancer. However, toxicity and acquired resistance to cisplatin have proven challenging in the treatment of ovarian cancer patients. EXPERIMENTAL DESIGN: Using a genetically engineered mouse (GEM) model of ovarian endometrioid adenocarcinoma (OEA) in combination with molecular imaging technologies, we studied the activation of the AKT serine/threonine kinase in response to long-term cisplatin therapy. RESULTS: Treatment of cells in culture and tumor-bearing animals with cisplatin resulted in activation of AKT, a key mediator of cell survival. Based on these results we investigated the therapeutic utility of AKT inhibition in combination with cisplatin, which resulted in enhanced and prolonged induction of apoptosis and in significantly improved tumor control compared to either agent alone. CONCLUSION: These results provide an impetus for clinical trials using combination therapy. To facilitate these trials, we also demonstrate the utility of diffusion-weighted MRI as an imaging biomarker for evaluation of therapeutic efficacy in OEA.